Adaptive minimum error least significant bit replacement method for steganography using JPG/JPEG and PNG files - Wamiliana, Wamiliana; Usman, Mustofa; Azram, Mohammad; Elfaki, Faiz Ahmed Mohamed; Hijriani, Astria; Panditatwa, Pandya (Sci.Int.(Lahore), 2015)
ABSTRACT: Nowadays, the security of data transmission is one of the important aspects in digital data transmission. In this era, sending messages via computers or other gadgets are highly used, the attackers can easily intercept the data during transmission process. Therefore, if there is a secret message, then it can be easily seen. One method for sending data without making curiosity is using the steganography where a secret message can be transmitted in such a way so that attackers are not aware of the existence of something in the message. In this research, we built a digital steganography system using Adaptive Minimum Error Least Significant Bit Replacement (AMELSBR) method. We use .jpg file for hiding the message, .png file for the output, .txt for the message. The procedures for applying AMELSBR method are Capacity Evaluation, Minimum Error Replacement and Error Diffusion. The result shows that the AMELSBR method is able to manage for hiding and restoring files without causing excessive distortion (noise) in stego image, and has a possibility of returning most files for image manipulation such as the change of image brightness and contrast for the black and white color dominan. However, the method is resistant to image cutting (crop).